Zone of Concept Image Differences in the Concept of Angles Formed by A Transversal at Undergraduate Level - Herizal, Herizal; Priatna, Nanang; Prabawanto, Sufyani; Jupri, Al (RANGE: Jurnal Pendidikan Matematika, 2025)
This study explored the differences in undergraduate students' concept images related to angles formed by a transversal intersecting any two lines compared with concept definition. Using diagnostic tests and interviews, the qualitative study with phenomenological design examined various student representations and common error patterns.  Students' answers were analyzed qualitatively to identify patterns, misconceptions, and variations in their concept images, followed by semi-structured interviews to explore their justifications. Participants were 35 second-semester students from the mathematics education study program at a state university in Aceh, Indonesia, who had completed the plane geometry course. The findings revealed significant variations in students' concept images, which were: (1) pairs of alternate interior/exterior angles, corresponding angles, and same-side interior/exterior angles were formed when two parallel lines were intersected by a transversal; (2) the measure of corresponding angles must be equal; (3) the measure of alternate interior angles must be equal; (4) the measure of alternate exterior angles must be equal; (5) the measure of same-side interior angles must be equal; and (6) misunderstanding and incorrectly identifying alternate exterior angles. These results highlight the importance of adapting teaching approaches to address differences in concept images and to better support students in mastering geometric concepts.  The novelty lies in its use of the Zone of Concept Image Differences to analyze the gap between students' concept images and formal definitions, offering insights into how to bridge these gaps in teaching.